PENGARUH MODEL PEMBELAJARAN THINK PAIR SHARE BERBANTUAN VIDEO ANIMASI TERHADAP PEMAHAMAN KONSEP MATERI BILANGAN BULAT PADA SISWA SEKOLAH DASAR - Nurazizah; Erni Nurjanah; Siti Aisyah; Santi Mardiana; Amelia Rahmatilah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mathematical conceptual understanding is one of the primary objectives of mathematics learning; however, it remains a significant challenge in education. The 2022 Programme for International Student Assessment (PISA) revealed that Indonesian students' mathematical literacy achievement was still below the average of OECD member countries. A similar condition was found among fourth-grade students at SDN Gandasoli, where only 40% of the students achieved the Minimum Mastery Criterion (KKM) in the topic of integers. The low level of conceptual understanding was presumed to result from learning activities that did not consistently provide opportunities for students to think independently, discuss with peers, and share ideas systematically, as well as the limited use of varied instructional media. This study aimed to determine students' conceptual understanding before and after the implementation of the Think Pair Share (TPS) learning model assisted by animated videos and to examine its effect on students' conceptual understanding. This study employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Pretest–Posttest Design. The sample consisted of 50 students, including 25 students in the experimental class and 25 students in the control class. Data were analyzed using descriptive statistics, normality and homogeneity tests, and the Independent Samples t-test. The findings indicated that the Think Pair Share (TPS) learning model assisted by animated videos had a significant effect on improving students' conceptual understanding of integers, with a significance value of 0.034 (< 0.05), a t-value of 2.179 (> 2.01), and an effect size of 0.759, indicating a moderate effect.